Drivers of vegetation and soil determine natural regeneration of a single plantation at different slope positions - Liang, Wenjun; Feng, Yonghan; Li, Fuming; Zhao, Yi; Zhu, Jingkang; Yao, Jiafeng; Chang, Chenlong; Wei, Xi (Frontiers in Forests and Global Change, 2023)
Promoting natural regeneration in artificial forest ecosystems is crucial for sustainable management. Understanding the fundamental mechanisms and drivers of tree regeneration is the prerequisite for promoting it effectively. This study worked with Larix principis-rupprechtii, a species considered difficult to regenerate. Twenty-four sample plots measuring 30 m × 30 m were established, with eight plots at each of the lower, middle, and upper slope positions, respectively. Field investigation and multivariate analysis were performed to uncover the regeneration traits in the plantations with abundant seedlings on the continuous slope. The results revealed that ground diameter and height of the regeneration (RGD and RH) were larger at the lower slope, with significant positive correlations to available nitrogen (contribution rate, CR: 0.858) and slope (CR: 0.652). In contrast, regeneration density (RD), representing the quantity of regeneration, was greater at the middle slope. Its significant impact factors were slope position (CR: -0.648) and herb diversity, represented by Pielou index (CR: 0.961). Stand density had a significant negative effect on regeneration, particularly at the upper slope, with contribution rates of -0.842 and -0.764 to RGD/RH and RD, respectively. Common contribution was found among the factors, with the largest contribution groups being the topographical and soil factors (CR:0.358). These findings provide valuable insights into the single species regeneration progress on northern mountainous slopes and offer essential information for developing facilitation methods for the natural regeneration in artificial forests.